Efficacy and safety of adalimumab biosimilar GP2017 in a 24-month treatment period for plaque psoriasis: real-life experience from Emilia-Romagna centers, Italy - Marco May Lee; Vito Di Lernia; Francesca Peccerillo; Federico Bardazzi; Michela Tabanelli; Michela Ricci; Davide Melandri; Monica Corazza; Francesca Satolli; Andrea Conti (Dermatology Reports)
Adalimumab (ADA), a monoclonal antibody targeting TNF-α, is effective in treating moderate to severe psoriasis. The emergence of biosimilars, such as GP2017 (Hyrimoz®), has raised concerns about their safety and efficacy compared to the originator. This two-year observational study evaluated the effectiveness and safety of GP2017 in 171 patients from Emilia-Romagna, Italy. Patients were divided into two groups: 78 transitioned from the ADA originator, and 93 were biologic-naive. Changes in the Psoriasis Area and Severity Index (PASI) were analyzed. In the switch group, PASI scores remained stable, while the naive group achieved significant improvements (PASI 75: 52% at 3 months, 89% at 6 months). Adverse events leading to discontinuation were rare. The findings confirm that GP2017 is as effective and safe as the ADA originator, supporting its use as a cost-effective alternative in the treatment of psoriasis. Biosimilars play a crucial role in promoting equitable access to biologic therapies.